Table of Content - - (Journal of Curriculum and Teaching Methodology, 2025)
Table of Content: • Future scenarios for teaching mathematical applications in artificial intelligence (robots as a model) at the secondary level in the Kingdom of Saudi Arabia Dr. Norah Shabeeb AboJalbah, Prof. Ghalya Hamad Al-Sulim • Exploring the Effect of Equitable Teaching Strategy on Perseverance in Solving Mathematical Problems: A Qualitative Study Mr. Mohammed Nejer Alotaibi , Prof. Mohammed Sanat Alharbi • Effectiveness of Using the Google Classroom Platform on Achievement and Motivation Toward Learning Science Among Eighth Grade Students in Palestine 1948 Ms. Rofaida Salah Khamaise, Ms. Bothaina Soliman Khatib • The effect of using the project-based learning (pbl) strategy on female student attitudes towards the subject of Physical education Dr. Maha Ahmad Alawrtani • The Use of Blended Learning and Its Impact on Developing Graduate Students’ Attitudes at King Abdulaziz University Toward Self-Directed Learning Ms. Nada Murizaq Al-Sulami • Professional Development of English Language Teachers in the Kingdom of Saudi Arabia in Light of the South Korean Experience: A Comparative Study Ms. Hind Marzouq Almutairi, Co-Prof. Tahani Khalid Al-Jubair